English Speech Training As An Effort To Improve Speaking Skills In Madura State Islamic Institute Students - Nurhaliza, Indriyani; Sa'i, Mad (SANISKALA : Jurnal Pengabdian Masyarakat, 2024)
English speech training is one of the efforts to improve students' speaking skills. This study aims to investigate the effectiveness of English speech training in improving speaking skills among students of Madura State Islamic Institute. The research methods used are speech practice, group discussion, presentation, and test. The results showed that English speech training can significantly improve students' speaking ability. This training can also increase students' confidence and motivation in communicating using English. The main objective was to give students the opportunity to practice public speaking. By practicing, students can overcome their low self-confidence and improve their speaking skills effectively. Therefore, English speech training can be an effective strategy in improving students' speaking skills. Hopefully, this training program can be continued and expanded to reach more students, in order to create a generation that is better equipped to communicate effectively in English.